Metodologi Normatif Dan Empiris Dalam Perspektif Ilmu Hukum - Yati Nurhayati; Ifrani Ifrani; M. Yasir Said (Scholar Center, 2021)
The purpose of this study is to determine the characteristics of normative and empirical legal research methods and when to use them in legal research. The method used in this research is the normative research, this methodwas chosen because the object of research is the principles of law, the rule of law, the theory and doctrine of legal experts. The results of this study is that normative research (doctrinal) is conceptualized and developed on doctrinal basis. This methodis interpreted as legal research at the level of norms, rules, principles, theory, philosophy, in order to find solutions to legal issues such as legal vacuum, conflict of norm, or vague norm. Meanwhile, empirical method is research with non-doctrinal characteristics carried out through field research. In this type of research, the data were collected which then processed according to the analytical techniques used which were outlined in a descriptive form in order to describe the actual condition of the reality of law as a social phenomena.